Ethnic differences in adiposity and diabetes risk – insights from genetic studies. (4th May 2020) - Yaghootkar, H.; Whitcher, B.; Bell, J. D.; Thomas, E. L.
Abstract: Type 2 diabetes is more common in non‐Europeans and starts at a younger age and at lower BMI cut‐offs. This review discusses the insights from genetic studies about pathophysiological mechanisms which determine risk of disease with a focus on the role of adiposity and body fat distribution in ethnic disparity in risk of type 2 diabetes. During the past decade, genome‐wide association studies (GWAS) have identified more than 400 genetic variants associated with the risk of type 2 diabetes. The Eurocentric nature of these genetic studies has made them less effective in identifying mechanisms that make non‐Europeans more susceptible to higher risk of disease. One possible mechanism suggested by epidemiological studies is the role of ethnic difference in body fat distribution. Using genetic variants associated with an ability to store extra fat in a safe place, which is subcutaneous adipose tissue, we discuss how different ethnic groups could be genetically less susceptible to type 2 diabetes by developing a more favourable fat distribution. Abstract : Content List ‐ Read more articles from the symposium: "Obesity and Type 2 Diabetes: Understanding the Role of Ethnicity".